The take - Yang, Kelly (Berkley, 2026)
"Maggie Wang, a broke young Asian American writer, needs a lifeline. Ingrid Parker, a veteran white Hollywood producer with her career on the edge, offers an irresistible deal: $3 million for ten experimental medical sessions promising to reverse her aging, using Maggie as a transfusion partner. For Ingrid, it's a chance to reboot her fading career. For Maggie, it's freedom--money to support her parents and finally finish her novel. What starts as a professional transaction exchanging blood quickly becomes a complex psychological dance. Maggie gains unprecedented access to Ingrid's hard-earned wisdom, while Ingrid sees in Maggie a potential protégé--and a weapon against an industry that's been trying to sideline her. As their relationship intensifies, they're forced to confront the harsh realities of race, age, and success. Who has the power to tell stories? And what are they willing to sacrifice to succeed?"-- Provided by publisher.